Performance Ratio Analysis: A National Study on Iranian Hospitals Affiliated to Ministry of Health and Medical Education. - Peivand Bastani; Soudabeh Vatankhah; Masoud Salehi (Tehran University of Medical Sciences, 2013)
This study was designed to present and compare Iranian hospitals` performance applying ratio analysis technique.This cross-sectional survey was conducted to present an instant image of 139 Iranian hospitals` performance status applying ratio analysis as one of the non parametric technical efficiency assessment methods in 2008. Data was collected using nine dimensional questionnaires supported by world wide web to achieve main hospital ratios. Final analysis was performed applying classic statistics and relevant statistical tests on significant level of 0.05.Four hospital performance indicators were estimated in the studied hospitals as follows: Bed turnover rate (BTR) was fluctuated from 64.5 to 114.8 times for hospitals located in rich and poor areas respectively. Moreover Bed Interval Rate (BIT) was calculated 1.36 versus 2.4 in the poor and rich areas. Average length of stay (ALS) was computed 1.82 for the poor regions but 3.27 for the rich ones furthermore, a positive statistical significant correlation was seen between ALS and the hospital size (P=0.001, r=0.28). Average bed occupancy rate (BOR) was 57.8% and its variation was from 31.4% to 64.5% depending on the hospital size so that there was a positive statistical significant relationship between the hospital size and BOR (P=0.006, r=0.32).Regarding that BOR, ALS, BTR and BIT along with mortality rates are mentioned as the most considerable performance indicators, applying analytic frameworks more than considering single and raw indicators are severely recommended.